Sistem Informasi Manajemen Legalisir Online Berbasis Website - Dairoh Dairoh; Riszki Wijayatun Pratiwi; Dwi Intan Af’idah; Sharfina Febbi Handayani; Ferian Andhika Toarsi (Infotekmesin, 2024)
Management and submission of legalization at the Harapan Bersama Polytechnic have not been computerized. The legalization process is carried out face-to-face by leaving legalized documents and returning them when the legalized documents are ready. This process is problematic because going to campus requires quite a long time, and there is no certainty or travel history from the management of legalized documents. The research objective is to build a legalization system to facilitate the process of implementing legalization in BAA units using the website-based waterfall method. This system validates alumni data in the form of NIM at registration, processes payments through payment gateways, pays for selected shipments, and tracks travel history from the submitted legalized documents. This system is called Simaleja, and there are two actors involved. As a result, the system runs according to the functions of the actors involved and has been tested. As for the results of the black box (actor) test, the system has been running according to the function of each actor, and the UI/UX usability results were obtained for 38 users, 82% of whom fall into the very good category.